Marvel-verse. Loki. - Macchio, Ralph; Lee, Stan, 1922-2018; Straczynski, J. Michael, 1954-; Rodi, Robert (Marvel Worldwide, Inc, 2021)
Collects a series of Marvel Comics featuring Loki, the Asgardian God of Mischief. Includes the story of the founding of the Avengers told from Loki's perspective, the tale of the time Loki tricked Thor into battling the Silver Surfer, and the tale of Kid Loki, who has turned over a new leaf.